2016
DOI: 10.15640/jssw.v4n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Social Support and Future Expectations among Young Adult Syrian Immigrants

Abstract: This study discuss the perceived social support, future expectations and the problems experienced before, during, and after forced immigration by young and adult Syrian immigrants who arrived in Turkey to seek temporary protection status due to the civil conflicts. The study was designed as qualitative inquiry and was implemented by applying the semi structured questionnaire with ten people through the face to face interviews. In terms of result of the study, it was determined that leaved their education befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…Problems associated with working life can reduce buying power and the standard of living. Syrian refugees generally report that house rents are very high, resulting in multiple families living together in poor living conditions, which further supports the findings of this study (Akar and Erdoğdu, 2019;Cifci et al, 2016;Genc and Özdemirkıran, 2015;Yıldız and Uzgören, 2016). Large differences between the living conditions of refugees and local populations can have negative effects on the accommodation process.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Problems associated with working life can reduce buying power and the standard of living. Syrian refugees generally report that house rents are very high, resulting in multiple families living together in poor living conditions, which further supports the findings of this study (Akar and Erdoğdu, 2019;Cifci et al, 2016;Genc and Özdemirkıran, 2015;Yıldız and Uzgören, 2016). Large differences between the living conditions of refugees and local populations can have negative effects on the accommodation process.…”
Section: Discussionsupporting
confidence: 85%
“…Although most of the refugees included in this study, in both provinces, reported working, approximately half of those in Hatay stated that they experienced economic problems. In this study and the literature, the economic lives of Syrian refugees have been found to be significantly affected, with many reporting relatively good economic conditions before the war but suffering great losses as a result of the war, with significant declines in income levels (Cifci et al, 2016). Related departments in Turkey have offered opportunities to improve the working lives and economic conditions of Syrian refugees, including that ability to apply for permission to work in various sectors, such as health, food, industry, agriculture, energy, buildings and transportation; workplaces, such as bakeries, forestry, mining, security and education; and in different geographic 2014).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation